Plasticidade sináptica homeostática na junção neuromuscular de camundongos ChAT-ChR2-EYFP jovens e idosos. - Wallace Lucio de Camargo (2019)
The increased amount of glutamate per vesicle in Drosophila is compensated by a decrease in the number of vesicles released by nerve stimulation. This compensatory mechanism capable of restoring synaptic homeostasis is called presynaptic homeostatic depression (PHD). We hypothesized that chronic increase in vesicular acetylcholine (ACh) release at the mouse neuromuscular junction (NMJ) may result in a compensatory decrease in evoked vesicular release. To test this, we used 3 and 24 months old ChAT-ChR2-EYFP (Hyper VAChT) mice that have increased levels of VAChT expression, and their wild-type controls (WT). All experimental procedures were approved by the Animal Ethics Committee (protocol number 106/2015 - CEUA). Spontaneous and evoked endplate potentials (EPPs) were evaluated at low (0.2 and 0.3Hz) and high (20 and 30Hz) frequency of stimulation at the NMJ of the diaphragm muscle. We also recorded, in voltage clamp, miniature plate currents (MEPCs). At 3 months of age, Hyper VAChT mice presented increased quantal size and frequency. The quantal content (QC) of Hyper VAChT mice (29 ± 2.5, mean ± SEM, n = 4 animals) showed no significant difference (p = 0.44) from the WT controls (31.5 ± 2.2, mean ± SEM, n = 4 animals). Synaptic depression was 19% higher in Hyper VAChT mice, and PTP was not statistically different. During tetanic stimulation, Hyper VAChT MEPPs areas were smaller than before the train of stimuli, while in the WT mice there was no change during high frequency stimulation. This suggests that the increased depression observed in Hyper VAChT mice is due a decrease effect of vesicular release. At 24 months of age, Hyper VAChT mice showed a significant decrease in QC (WT = 41 ± 3.5, mean ± SEM, n= 5 animals; Hyper VAChT = 29 ± 4.1, mean ± SEM, n = 3 animals; p = 0.07). Synaptic depression and postetanic potentiation (PTP) were not statistically different. These results show that Hyper VAChT mice compensated for the increase in quanta size in two different ways: at 3 months, EPPs at high frequency stimulation decreased by increased desensitization or decreased ACh per vesicle. While at 24 months, we observed a decreased in QC. Our data show that longterm increase in ACh per quantum triggers the pre-synaptic mechanism of DHP seeing as a decrease in the number of vesicles released. This mechanism is not seeing in young animals, which keep the same postsynaptic output through other mechanism.